(untitled) (Palimpsesto, 2018)
This research approaches the protests against the dictatorship of Augusto Pinochet in Chile, from the perspective of the gender role configuration for men and women within this process. The analysis approaches the tension and relationship between these roles and class, political placement about the use of violence and the mainly masculine opposition parties’ strategies. Based on photographic material, personal interviews and documentation, a landscape of politicization and protest activities is drafted for the capital city of Santiago, including spaces such as urban slums and universities, volunteer work and church organizations, always focusing in men’s and women’s different tasks, taking these roles into tension with the traditional gender ideas.